2009
DOI: 10.1007/s00467-009-1279-6
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of urinary tract infection with urinary neutrophil gelatinase associated lipocalin

Abstract: Neutrophil gelatinase associated lipocalin (NGAL) is a protein identified in human neutrophil granules. The aim of the study was to assess whether urine level of NGAL (uNGAL) could represent a novel, reliable marker of urinary tract infection (UTI) and to determine the optimal cutoff level for uNGAL to predict UTI in children. Sixty patients with symptomatic UTI and 29 healthy controls were enrolled the study. Urine NGAL was measured by enzyme-linked immunosorbent assay. A dimercaptosuccinic acid (DMSA) radion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
103
1
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 18 publications
5
103
1
8
Order By: Relevance
“…This was consistent with our previous findings (18,19). Conflicting data have shown that uNGAL is elevated in patients with renal scarring compared to the level in those without scarring (1,37). In patients diagnosed with VUR without evidence of current UTI, uNGAL levels were also significantly higher compared to those in controls (37).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This was consistent with our previous findings (18,19). Conflicting data have shown that uNGAL is elevated in patients with renal scarring compared to the level in those without scarring (1,37). In patients diagnosed with VUR without evidence of current UTI, uNGAL levels were also significantly higher compared to those in controls (37).…”
Section: Discussionsupporting
confidence: 92%
“…Ichino et al (17) demonstrated experimentally that uNGAL levels in rats increased in both the early and extensive fibrosis stages of pyelonephritis, suggesting that uNGAL might also be useful as a marker of APN and renal scarring in humans. Indeed, we, and other investigators, have demonstrated that uNGAL can be a useful predictor for detecting UTIs in children (1,18). In patients with febrile UTIs, increased uNGAL levels were related to UTI severity, and levels decreased following antibiotic treatment.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…Recent studies from Korea [5] and Turkey [6] showed that NGAL might be a good marker for UTI diagnosis but studies suffer from small number of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, novel biomarkers are emerging as alternative tools in the diagnosis of UTI (6)(7)(8)(9)(10)(11)(12)(13), and as predictors of its complications such as vesico-ureteric reflux (VUR) (14)(15)(16)(17)(18) as well as renal parenchymal injury (19)(20)(21)(22). Reports also show that febrile UTI in children activate an interleukin 6 (IL-6) and interleukin 8 (IL-8) responses, thus adding the estimation of these cytokines in the diagnostic trajectory of the disease (23,24).…”
Section: Introductionmentioning
confidence: 99%